Opioid activation in the lateral parabrachial nucleus induces hypertonic sodium intake - De Oliveira, L. B. [UNESP]; De Luca, L. A. [UNESP]; Menani, José Vanderlei [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Opioid mechanisms are involved in the control of water and NaCl intake and opioid receptors are present in the lateral parabrachial nucleus (LPBN), a site of important inhibitory mechanisms related to the control of sodium appetite. Therefore, in the present study we investigated the effects of opioid receptor activation in the LPBN on 0.3 M NaCl and water intake in rats. Male Holtzman rats with stainless steel cannulas implanted bilaterally in the LPBN were used. In normohydrated and satiated rats, bilateral injections of the opioid receptor agonist beta-endorphin (2 nmol/0.2 mu l) into the LPBN induced 0.3 M NaCl (17.8 +/- 5.9 vs. saline: 0.9 +/- 0.5 ml/240 min) and water intake (11.4 +/- 3.0 vs. saline: 1.0 +/- 0.4 ml/240 min) in a two-bottle test. Bilateral injections of the opioid antagonist naloxone (100 nmol/0.2 mu l) into the LPBN abolished sodium and water intake induced by 13-endorphin into the LPBN and also reduced 0.3 M NaCl intake (12.8 +/- 1.5 vs. vehicle: 22.4 +/- 3.1 ml/180 min) induced by 24 h of sodium depletion (produced by the treatment with the diuretic furosemide s.c.+sodium deficient food for 24 h). Bilateral injections of 13-endorphin into the LPBN in satiated rats produced no effect on water or 2% sucrose intake when water alone or simultaneously with 2% sucrose was offered to the animals. The results show that opioid receptor activation in the LPBN induces hypertonic sodium intake in satiated and normohydrated rats, an effect not due to general ingestive behavior facilitation. In addition, sodium depletion induced 0.3 M NaCl intake also partially depends on opioid receptor activation in the LPBN. The results suggest that deactivation of inhibitory mechanisms by opioid receptor activation in the LPBN releases sodium intake if excitatory signals were activated (sodium depletion) or not. (C) 2008 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: beta-endorphin; sodium appetite; water intake; naloxone; satiety